ANALISIS PERENCANAAN KEBUTUHAN BAHAN BAKU PALLET KAYU DENGAN MATERIAL REQUIRMENT PLANNING DI PT. MITRA ATHMAR BERKAH - Mauludi, Refan; Huda, Miftahul; Doto, Doto; Panulisan, Bambang Setyo (LPPM Universitas Bina Bangsa, 2024)
PT. Mitra Athmar Berkah is a company that produces wooden pallets. In 2022, this production reach 38.201 units. Over time, several problems have occurred, one of which is the occurrence of shortages of raw material inventory resulting in delays in the production process. The purpose of conducting this research is to produce planning for the raw material requirements for pallet. The method used in this study is Material Requirement Planning (MRP) with Lot sizing used, namely Lot for Lot (LFL), Economic Order Quantity (EOQ), and Period Order Quantity (POQ). The data processing and analysis results show that the chosen forecasting method is Exponential Smoothing , because the error values of MAD, MSE, and MAPE have the smallest error values compared to other forecasting methods. While the lot sizing on the MRP method chosen is the Lot for Lot (LFL) method because it produces a total inventory cost of IDR 420,080,525.00. The conclusion of this study is to obtain raw material requirements for the coming year and to know the optimal amount of inventory costs from the selected lot sizing